2012
DOI: 10.1080/09515089.2011.631995
|View full text |Cite
|
Sign up to set email alerts
|

Order effects in moral judgment

Abstract: Explaining moral intuitions is one of the hot topics of recent cognitive sciences. In the present article we focus on a factor that attracted surprisingly little attention so far, namely the temporal order in which moral scenarios are presented. We argue that previous research points to a systematic pattern of order effects that has been overlooked until now: Only judgments of actions that are normally regarded as morally acceptable are affected by the order of presentation. Additionally, this is only the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 41 publications
5
58
0
Order By: Relevance
“…Specifically, while there was no difference in judgment of whether one should sacrifice oneself or someone else, participants were more likely to say that it is wrong to sacrifice someone else than themselves. There was no evidence of an order effect which is in line with recent findings showing that order effects in moral judgment may be relatively uncommon and limited to a narrow set of circumstances (Wiegmann, Okan, & Nagel, 2012). However, the results suggest that the strength of the otherserving bias may depend on used scenarios since we found evidence for the effect only in two dilemmas.…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, while there was no difference in judgment of whether one should sacrifice oneself or someone else, participants were more likely to say that it is wrong to sacrifice someone else than themselves. There was no evidence of an order effect which is in line with recent findings showing that order effects in moral judgment may be relatively uncommon and limited to a narrow set of circumstances (Wiegmann, Okan, & Nagel, 2012). However, the results suggest that the strength of the otherserving bias may depend on used scenarios since we found evidence for the effect only in two dilemmas.…”
Section: Discussionsupporting
confidence: 79%
“…Although not common in the moral judgment domain, there is work indicating that judgments are sensitive to the order in which information is presented (Austin, Ruble, & Trabasso, 1977;Feldman et al, 1976;Petrinovich, & O'Neill, 1996;Sinnott-Armstrong, Mallon, McCoy, & Hull, 2008;Wiegmann, Okan, & Nagel, 2012). Wiegmann et al (2012) point out two types of order effects (Primacy & Recency effects; Sequential effects).…”
Section: Ordermentioning
confidence: 99%
“…Wiegmann et al (2012) point out two types of order effects (Primacy & Recency effects; Sequential effects). First, developmental studies show that the first and last items of information presented in a moral scenario lead to the most extreme moral judgments (Austin et al, 1977;Feldman et al, 1976).…”
Section: Ordermentioning
confidence: 99%
“…A second study, Schwitzgebel and Cushman (2012) (hereafter 'SC'), offers a test of this formulation of the expertise defense. Previous research (Petrinovich and O'Neill 1996;Lombrozo 2009;Liao et al 2011;Wiegmann et al 2012) had found that nonphilosopher subjects' moral judgments were sensitive to order effects: their intuitive responses to test cases depended upon the order in which these cases were presented. It seems clear that order effects are a form of distortion; presumably the moral valence of a particular action does not depend upon whether the intuiter has just thought about some other action.…”
Section: Empirical Evidence Against the Expertise Defensementioning
confidence: 99%
“…Such arguments depend crucially on evidence from psychology and experimental philosophy, showing that people's intuitions are sensitive to a host of things which seem irrelevant to the truth of philosophical theories. For instance, intuitions about moral permissibility and knowledge-possession seem to be sensitive to the order in which the intuiter encounters test cases (Petrinovich and O'Neill 1996;Swain et al 2008;Lanteri et al 2008;Lombrozo 2009;Liao et al 2011;Wiegmann et al 2012) or whether the intuiter imagines herself as a bystander or actor in a test case (Nadelhoffer and Feltz 2008).…”
Section: Intuitions Empirical Challenges and The Expertise Defensementioning
confidence: 99%